ANALISIS PENGUKURAN KERJA UNTUK MENGOPTIMALKAN PRODUKTIVITAS MENGGUNAKAN METODE TIME AND MOTION STUDY - Khadijah, Intan; Kusumawardhani, Amie (Faculty of Economics and Business Diponegoro University, 2016)
Productivity is one of benchmarks to determine the development of a company. This study aimed to analyze work measurement help to optimize productivity in Ayasy snack and bakery. Sample in this study, four products that are most often ordered by the customers of Ayasy snack and bakery. The analytical method used is time and motion study. The results of the analysis technique of time and motion study, shows that productivity can be improved by determining the standard time and job design in improving efficiency. Using time study, result of standard time can increase productivity by 106%. Motion study techniques also increased productivity up to 3.10% when company implemented the proposed method in process chart. Productivity can be increased by continuously improving methods of work , the layout and optimize the equipment capacity of Ayasy snack and bakery.